The effect of freezing rate temperatures and kind of extenders on the quality of frozen sperm of Priangan Goat - I Herdiawan (Jurnal Ilmu Ternak dan Veteriner, 2004)
The study has been conducted on Animal Reproduction Laboratory of Animal Husbandry Faculty, Padjadjaran University, in Jatinangor, Sumedang, West Java to find out the interaction of freezing rate temperatures and kind of extenders on frozen semen quality after thawing. Factorial completely randomized design was used in the experimant with first factor was freezing rate temperatures (7, 13, and 200C/mins), and second factor was semen extenders (egg yolk-citrate and egg yolk tris-base). Each treatment had four replication. Variables observed were sperm mobility and abnormality, aerosome and membrane sperm cell integrities, sperm viability incubated in water for four to seven hours, and sperm recovery after thawing. Results of statistical analysis show that there was interaction between freezing rate of 13°C/mins and egg yolk tris-base on sperm motility. However, other variables did not indicated interactions. The best sperm motility was observed from the freezing rate 13°C/mins on egg yolk tris-base, it had recovery value of 52.53%. Main effect analysis show that freezing rate 13°C/mins had highly significantly results than others treatment (P<0.01) on lowest abnormality, best integraty of acrosome and membrane cell, viability in water incubation for four and seven hours and recovery value after thawing, subsequently they were 16.04, 42.88, 37.90, 35.54, 23.51 and 50.92%. Main effect on extender showed that egg yolk tris-base significantly (P<0.05) 7 best for lowest abnormality west for integrity of acrosome and membrane cell, viability in water incubation for four and seven hour, sperm recovery value after thawing subsequently they were 19.05, 39.17, 35.86, 32.30, 21.12 and 50.00%.  Key words: Freezing rates, extender, quality of frozen semen, Priangan goat